MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA CINANGKA, KECAMATAN CIAMPEA, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Mohammad Sutriansyah (SAHID DEVELOPMENT JOURNAL, 2022)
This community service aims to program access to sharia financing for Micro, Small and Medium Enterprises (MSMEs) in Cinangka Village, Ciampea District, Bogor Regency. The subjects of this community service are the people of Cinangka Village, Ciampea District, Bogor Regency, West Java Province, especially those included in MSMEs. In community service, activities are carried out based on participatory methods involving the community as the subject. The result of community service is that in addition to the community becoming more aware and understanding of sharia financing for MSMEs, the community also knows and understands Islamic financial institutions such as Islamic banks and Islamic microfinance institutions which can be used as places to apply for sharia financing. Therefore, sharia banks and sharia microfinance institutions must accompany business operations and be intensely involved in monitoring and ensuring that MSMEs that receive sharia financing assistance are able to manage their finances properly.